2021
DOI: 10.3390/su132313045
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Solid Waste Generation in the Perspectives of Socioeconomic and People’s Behavior: A Case Study in Serdang, Malaysia

Abstract: Malaysia has enforced several phases of Movement Control Order (MCO) as a quarantine period since 18 March 2020 with the intended purpose of containing the coronavirus disease (COVID-19) outbreak. The quarantine has affected people’s daily lives with frequent job dismissal and retrenchment due to the struggling economic conditions of particularly small and medium businesses. This study aimed to understand the impact of MCO on solid waste management in Serdang, Selangor from the aspects of socioeconomic and peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Brohan et al (2021) summarised the impact of COVID-19 on municipal solid waste in Peninsular Malaysia. It was found that the municipal solid waste began to increase when the movement control order (MCO) reached the conditional and recovery stages (Arumugam et al, 2021;Brohan et al, 2021). It indicates that lifestyles can have an impact on the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Brohan et al (2021) summarised the impact of COVID-19 on municipal solid waste in Peninsular Malaysia. It was found that the municipal solid waste began to increase when the movement control order (MCO) reached the conditional and recovery stages (Arumugam et al, 2021;Brohan et al, 2021). It indicates that lifestyles can have an impact on the environment.…”
Section: Introductionmentioning
confidence: 99%
“…According to a study, in Selangor, Malaysia, public awareness of sorting household waste is relatively high. However, that does not always occur in practice, especially for residents of shared apartments occupying vertical housing [3]. In this sense, there has been a gap between knowledge and behaviour.…”
Section: Soft Law In Covid-19 Handling: a Literature Reviewmentioning
confidence: 99%
“…Nowadays, significant factor considerations must be considered before implementing food waste disposal units as a wide-ranging solid waste management option, as solid waste is related to emissions of greenhouse gasses and other environmental damage. Continued research and development in food waste could better manage this choice to become a sustainable alternative to landfilling, incineration, and composting (Ismail et al, 2020a;Arumugam et al, 2021).…”
Section: Introductionmentioning
confidence: 99%